Conceptualising learning in social virtual worlds: an ethnography of three groups in Second Life - Tay, W (2012)
This thesis presents an ethnographic investigation of how people organise themselves into groups in social virtual worlds and how learning occurs through such organisation. In particular, emphasis is placed on examining the learning processes occurring in both the individuals and the groups that they belong to. To examine this overarching question, an ethnographic-based study of three informal, self-organising groups was conducted over a nine-month period in the social virtual world, Second Life, with participant observation and in-world semi-structured interviews as the main data collection methods. The study is guided by the following research questions: 1) what are the salient attributes of the three groups and how have they changed as the groups developed over time?; 2) what can be observed of the ways in which learning occurs along the three planes: individuals, interpersonal relations, and group?; and 3) how does group development affect learning, and vice versa? The findings indicate that on an individual level, learning was observed to have occurred as members developed their own practice, knowledge and skills, engaged in shared practices, and felt a sense of becoming and belonging in their respective groups. On an interpersonal level, learning occurred as members worked on managing relationships with other members, negotiating and resolving conflicts and engage in collaborative projects. On a group level, learning was observed to have occurred as the group members worked on modifying norms and shared values, creating new connections, adopting new technologies, increasing responsiveness to conflicts and adaptability to change, and increasing group cohesiveness. The findings draw together individual and group cognition, as well as the social and environmental context, and stress that all of these are pertinent in advancing our understanding of the ways people learn in social virtual worlds. The importance of this thesis lies in its contributions to the emerging literature of virtual worlds, by developing a conceptual understanding of how we think about learning in social virtual worlds like Second Life. A framework that is widely applied in the literature for examining groups is the Community of Practice (CoP) model (1991; Wenger, 1998). While CoP offers important insights, I argue that it is not applicable to all groups in social virtual worlds. I suggest instead that learning be examined along three planes as suggested by Rogoff (1995; 1998). These three planes of analysis can be used to explain changes in a group's attributes as it develops and mature over time. Doing so will open up new avenues and opportunities for us to explore learning within the social virtual worlds, especially in the light of group development. Drawing on the literature review and findings of the three groups studied, I present a framework that conceptualise learning in relation to group development in the virtual world environment, with the aim of contributing to this nascent area of educational research.